PERENCANAAN SQUEEZE CEMENTING JOB PADA SUMUR “RF-L”, LAPANGAN “D” DENGAN MENGGUNAKAN METODE BALANCE PLUG - Ripal Rombe; Rohima Sera Afifah; Muhammad Nur Mukmin; Aris Luqman Tryana; Nijusiho Manik; Rizky Kurniawan (PETROGAS: Journal of Energy and Technology, 2026)
This research aims to design a squeeze squeeze cementing job for well “RF-L” in field “D” using the balance plug method to isolate the MFS-8 formation layer, which has shown a decline in productivity and an increase in water production. The research method using the balance plug technique . The calculations were based on casing, tubing, perforation, and reservoir pressure data. The results indicate that the squeeze cementing operation requires 46 sacks of Class G cement with a total slurry  volume of 9.402 bbl and 5.5 bbl of mixing water. The volume of spacer ahead was 12.81 bbl and spacer behind was 1.09 bbl, while the displacement fluid volume was 4.5 bbl (after subtracting 1 bbl of underdisplacement). Reverse circulation of 5.2 bbl was performed to clean residual slurry  from the tubing. Hesitation and Waiting on Cement (WOC) were applied to ensure the cement hardened properly in the target zone without damaging the formation